Producing Glutathione, Carotene and Proline in Chlorella sorokinana on the Effect of Salt Stress and Different Growth Phases - Fadeel, Zeina Gany (Nabatia, 2025)
This study explained the effect of Nacl added to the culturing medium Bg11 during the growth of Chlorella sorokinana. It showed that there was a direct relationship between the increase in the concentration of Nacl and both glutathione and proline; the maximum concentrations recorded were 75.234 mg.l-1 and 27.218 mg L-1, correspondingly, at the level of 300 ppm. Conversely, The maximum level of carotene identified was 1.6 mg.l-1 when using a dosage of 100 ppm. The findings from the comparison of growth phase dates indicated that the peak values for glutathione, proline, and carotene were 71.238, 22.359, and 1.625 mg.l-1 respectively during the second growth phase. The results of the interaction analysis revealed that the highest levels of both glutathione and proline were 78.873 and 30.166 mg.l-1 respectively when the concentration was 300 ppm in the second growth phase. Regarding carotene, the maximum value reached was 2.5 mg.l-1 at a concentration of 100 ppm during the second growth phase. From the present study, we conclude that the Nacl concentration of 300 ppm was the most suitable for obtaining the highest production of glutathione and proline, whereas the optimal Nacl concentration for obtaining the highest production of carotene was at 100 ppm. Finally, growth phases in the second phase of growth was the best age phase for getting the highest production of glutathione, proline and carotene.